A SYSTEMATIC REVIEW OF THE APPLICATION OF THE INSANITY DEFENCE IN MURDER CASES: IMPLICATIONS FOR THE CRIMINAL JUSTICE SYSTEM AND MENTAL HEALTH IN INDONESIA - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
The application of the insanity defence in murder cases in Indonesia highlights the challenges and implications arising from the application of this law. This study examines the consistency and effectiveness of the insanity defence in Indonesia and its impact on the criminal justice system and mental health. The review shows that although Indonesian law recognises the insanity defence, its implementation is often inconsistent and not supported by an adequate mental health assessment system. This results in unfairness in the handling of murder cases involving suspects with mental illness, as well as the continued stigmatisation of people with such disorders. The implications of these findings are significant for improving the justice and mental health systems in Indonesia. Better integration between the legal system and mental health services is needed to ensure the application of the insanity defence is fair and human rights compliant. This study recommends improved training for law enforcement, as well as strengthened coordination with mental health professionals to support effective rehabilitation for individuals with mental illness. This is expected to improve the fairness and protection of individual rights in the application of the insanity defence in Indonesia.